Agrostology Approaches to Pasture Management and Feed Calculation for Sheep: A PRISMA Review - Laeli Fitrah (International Journal Multidisciplinary Science, 2026)
Sheep farming plays a crucial role in smallholder livestock systems across tropical regions, including Indonesia, where forage availability and feeding efficiency remain major challenges. Agrostology, as the study of pastures and forage resources, provides essential insights into sustainable feed planning and pasture management strategies. This study conducts a Systematic Literature Review (SLR) using the PRISMA 2020 guidelines to synthesize recent evidence (2020–2025) on forage-based feed calculation and pasture management for sheep. A total of 19 peer-reviewed articles were identified from open-access databases, with inclusion criteria focusing on sheep nutrition, forage productivity, and pasture utilization, supplemented with comparative studies on cattle for broader context. Findings reveal that integrating nutrient requirement models (e.g., NRC, region-specific standards) with locally adapted forage species significantly improves sheep productivity while reducing feeding costs. Moreover, rotational grazing, silvopastoral systems, and mixed forage strategies enhance pasture resilience, nutritive value, and animal performance in tropical environments. Comparative evidence from cattle-based systems further emphasizes the relevance of forage diversity and strategic supplementation in sustaining productivity under seasonal feed fluctuations. Despite these advances, gaps remain in the adoption of participatory feed planning tools, context-specific pasture evaluation, and digital-based feed calculation models for smallholders. This review highlights the importance of combining agrostological approaches with community-based feed management to improve the sustainability of sheep production. The insights are particularly relevant for smallholder systems in regions such as Kuningan, West Java, where forage potential exists but requires structured feed planning.